Innovation Management in Insurance Brokerage Companies in The Development of Retirement Credit Life Insurance - Budirachman, Ardhyanto (Green Publisher Indonesia, 2025)
The transformation of the financial services sector, driven by digitalization and regulatory dynamics, has placed new demands on insurance brokerage firms to act as intermediaries and innovation-driven strategic partners. This study aims to analyze innovation management within Indonesian insurance brokerage companies that develop retirement credit life insurance, particularly in the context of regulatory pressure and digital transformation. Employing a qualitative case study method, data were collected through in-depth interviews, observations, and document reviews involving strategic-level informants. Thematic analysis revealed three main findings: (1) innovation efforts are primarily focused on digitizing service processes and integrating systems with banks to enhance efficiency and customer satisfaction; (2) regulations issued by Indonesia’s Financial Services Authority (OJK) act as catalysts for innovation, pushing firms to adopt transparent, tech-based systems; and (3) ambidextrous strategies are adopted to balance service exploitation and innovation exploration. These findings validate the relevance of Open Innovation, Regulatory-Driven Innovation, and Organizational Ambidexterity in the insurance brokerage sector. Practically, this study offers strategic insights for brokerage firms to collaborate with insurtechs and banks, while also informing regulators to develop flexible policies that foster innovation without compromising consumer protection. The research contributes to bridging the gap in the literature on innovation management in insurance brokerages under strict regulatory constraints.